The Role of Religious Institutions in Promoting Social Welfare in Indonesia - Hariawan Adji (Universitas Airlangga, 2021)
This paper discusses religion from social anthropological point of view. Religious teachings are not seen as something sacred and transcendent, but something worldly and immanent as a source of motives of its followers while religious institution are seen as religion inspired social institutions that have their role in the society. The method used in this study is fieldwork. The data are collected though participative observation and interview. Literary study is also done to complete the data and check the data collected from the field. The result of this study shows that due to this nature, in promoting social welfare, religion through its teachings and institutions work on two levels: spiritual and practical level. Though this paper uses the Indonesian Catholic Church as an example, other religious institutions may have similar programs to participate in the process of making the world better place for everybody.